Beyond The Immigration Services: The Role of the International Center in Promoting Intercultural Programs for International Student Success - Marzul Hidayat (Universitas Jambi, Indonesia, 2022)
International students have come to a specific country for a specific period of time for the purpose of obtaining a degree. The success for international students who are from various academic and social backgrounds is not only about educational achievement but also regarding social connection in a new academic community. One of the centers that promotes the success for international students is the International Center in every university. The purpose of this inductive study was to investigate the role of the International Center (IC) in promoting international students’ success in college academically and non-academically. The theoretical framework of Tinto’s (1975) student integration theory in higher education was used to guide the study while the data were collected through Interviews and observations with the director, the intercultural programs and training coordinator, and one international student adviser. The interview data and field notes obtained were organized and analyzed for regularities, patterns, and emerging topics. The results of the data analysis produced six salient themes: mission and vision, pre-arrival programs, arrival programs, ongoing programs, preventive programs, international students’ challenges. The implications of the study are also discussed.